A clinically viable vendor-independent and device-agnostic solution for accelerated cardiac MRI reconstruction. (August 2021) - Martín-González, Elena; Moya-Sáez, Elisa; Menchón-Lara, Rosa-María; Royuela-del-Val, Javier; Palencia-de-Lara, César; Rodríguez-Cayetano, Manuel; Simmross-Wattenberg, Federico; Alberola-López, Carlos
Highlights: Device-agnostic, fully functional solution for MR reconstruction. Times are comparable to BART with nVidia and AMD devices. Multi-device implementation of groupwise registration algorithm. Existing implementations are pairwise and device-specific. Multi-device, multi-coil NESTA implementation. No assumption about matrices involved are projectors. O ( 1 ) [ Plea se dele te this equa tion ] Developers focus on kernel development thanks to OpenCLIPER's architecture and abstraction of device maintenance work. OpenCLIPER enables the use of HIP libraries over pure OpenCL data objects, so code can be integrated in other projects. Abstract: Background and objective : Recent research has reported methods that reconstruct cardiac MR images acquired with acceleration factors as high as 15 in Cartesian coordinates. However, the computational cost of these techniques is quite high, taking about 40 min of CPU time in a typical current machine. This delay between acquisition and final result can completely rule out the use of MRI in clinical environments in favor of other techniques, such as CT. In spite of this, reconstruction methods reported elsewhere can be parallelized to a high degree, a fact that makes them suitable for GPU-type computing devices. This paper contributes a vendor-independent, device-agnostic implementation of such a method to reconstruct 2D motion-compensated, compressed-sensing MRI sequences in clinically viable times. Methods: By leveraging our OpenCLIPER framework, the proposed system works in any computing device (CPU, GPU, DSP, FPGA, etc.), as long as an OpenCL implementation is available, and development is significantly simplified versus a pure OpenCL implementation. In OpenCLIPER, the problem is partitioned in independent black boxes which may be connected as needed, while device initialization and maintenance is handled automatically. Parallel implementations of both a groupwise FFD-based registration method, as well as a multicoil extension of the NESTA algorithm have been carried out as processes of OpenCLIPER. Our platform also includes significant development and debugging aids. HIP code and precompiled libraries can be integrated seamlessly as well since OpenCLIPER makes data objects shareable between OpenCL and HIP. This also opens an opportunity to include CUDA source code (via HIP) in prospective developments. Results : The proposed solution can reconstruct a whole 12–14 slice CINE volume acquired in 19–32 coils and 20 phases, with an acceleration factor of ranging 4–8, in a few seconds, with results comparable to another popular platform (BART). If motion compensation is included, reconstruction time is in the order of one minute. Conclusions : We have obtained clinically-viable times in GPUs from different vendors, with delays in some platforms that do not have correspondence with its price in the market. We also contribute a parallel groupwise registration subsystem for motion estimation/compensation and a parallel multicoil NESTA subsystem for l 1 − l 2 -norm problem solving.